2014
DOI: 10.1590/0037-8682-0069-2013
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of post-discharge surgical site infections among patients from a teaching hospital

Abstract: Introduction: Surgical site infections (SSIs) often manifest after patients are discharged and are missed by hospital-based surveillance. Methods: We conducted a case-reference study nested in a prospective cohort of patients from six surgical specialties in a teaching hospital. The factors related to SSI were compared for cases identifi ed during the hospital stay and after discharge. Results: Among 3,427 patients, 222 (6.4%) acquired an SSI. In 138 of these patients, the onset of the SSI occurred after disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The variation in incidence rates observed between the literature and the data from this study may be related to the presence of different epidemiological surveillance systems at national level 2 , 14 - 15 , Post-discharge Surveillance 8 , 16 (PDS) and possible occurrence of underreporting of SSI.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…The variation in incidence rates observed between the literature and the data from this study may be related to the presence of different epidemiological surveillance systems at national level 2 , 14 - 15 , Post-discharge Surveillance 8 , 16 (PDS) and possible occurrence of underreporting of SSI.…”
Section: Discussionmentioning
confidence: 62%
“…However, it was lower than in studies carried out in data reported from India and Turkey, which presented an SSI incidence of 5.0% 16 ) and 4.1% 17 , respectively. Two Brazilian studies involving SSI in general surgeries had higher rates than the identified incidence and compared to international researches, ranging from 6.4% 8 to 11.0% 3 .…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In this study, the incidence of post-discharge SSIs in the women surveyed was 5.8%. At the university hospital of the College of Medicine of Botucatu, 62.2% of gynecological SSIs began after hospital discharge 5 . Thus, post-discharge monitoring after surgical procedures contributes to increased reporting of SSI incidence.…”
Section: Discussionmentioning
confidence: 99%